POTENSI ARANG AKTIF DARI LIMBAH TULANG KAMBING SEBAGAI ADSORBEN ION BESI (III), KADMIUM (II), KLORIDA DAN SULFAT DALAM LARUTAN - Fiqih Khairani; Itnawita '; Subardi Bali (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Goat bone waste had not been used optimally up till now it is only used as handicraft. Chemically the goat bone contains 22% of organic matrix that is possible to be used as a raw material for activated charcoal. The activated charcoal of goat bone was made of through two stages that are carbonization at a temperature of 700oC and activation using Na2CO3 with various concentration of 2,5%; 5,0% and 7,5% at a temperature 800oC. From characterization, it was obtained that activation using 5,0% Na2CO3 gave a good characteristics with the value of moisture content is 7,5269%, ash content is 19,1423%, the adsorption of iodine is 200,2239 mg/g and a surface area is 91,1557 m2/g. The activated charcoal at a concentration of 5,0% Na2CO3 was used to adsorp ions of iron, cadmium, chloride and sulfate based on various concentration of 100, 200, 300, 400, 500 and 600 ppm that were contacted for 24 hours. The optimum adsorption ability of the activated charcoal of goat bone was obtained at a concentration of 200 ppm with the adsorption cations of iron ions (99,8875%) and cadmium ions (99,9609% ) that were analyzed using an Atomic Absorption of Spectrophotometer (AAS), while sulfate ions (77,7976%) that was analyzed using a UV-VIS Spectrophotometer. However, the adsorption of activated charcoal goat bone was not good enough for chloride ions (11,9528%) that was analyzed by Argentometry (Mohr) method.